Analisis Aborsi Bagi Perempuan Menikah Di Kecamatan Tanjung Pura - Fira Humaira (Peduli Riset dan Pengabdian Masyarakat, 2023)
This thesis discusses abortion. Abortion is an act of abortion. In Indonesia, this action is a prohibited act and is included in the chapter on crimes against life in the RKUHP and the Health Law. Even though it is legally prohibited, in reality abortions are still mostly carried out by women for various reasons due to the fact that existing regulations and laws are not in accordance with the reasons that force women to have abortions. In general, abortion can be divided into 2 types, namely accidental abortion and intentional abortion. Accidental abortion is an accidental abortion that occurs without any action.While intentional abortion is an abortion that occurs as a result of an action. Abortion in this second form can be divided into 2 types, namely abortion artialis therapicus and abortion procatus criminalis. The findings of research on P, a housewife who had an abortion for reasons of close pregnancy and fear of endangering the child to be born. This statement raises several questions: What is the law on abortion for married women? How is the practice? Is the treatment justifiable? To obtain answers to these questions, this study used a qualitative descriptive approach with data collection techniques in the form of observation and interviews. Here the researchers took several legal sources such as: the Qur'an, MUI Fatwa, and the Health Law in solving existing problems. The research collected data from interviews and other research methods. Based on the analysis of these data it can be concluded that abortion law in Islam and the Health Law allows it to be done if it is in an old and emergency situation, otherwise it cannot be justified